The anthropometric data importance to karate-do - Teodoru, M.; Petre, R. (Science, Movement & Health, 2013)
Within our scientific approach, we took into account the most important anthropometric measurements that can influence the strike efficiency in relation to the fighter`s stance during a Karate-do competition. Methods. To perform the anthropometric measurements (age, weight, height, length of the upper and lower limbs), we used the same tools for all the 10 selected subjects, top performance athletes at the national level. Results. The data collected through anthropometric measurements are better valorized when they are included into different formulae, in order to determine a series of anthropometric indices, such as those related to proportionality, which aim at assessing the growth and development phenomena. We can thus make comparisons among subjects or groups of subjects, relying on some objective criteria. For each of these values, we calculated the following indicators: arithmetical mean, median, standard deviation, mean deviation, dispersion, amplitude, coefficient of variation. Conclusions. Statistical analyses showed that our sample was homogeneous in relation to the subjects` age, height, length of the upper limb, length of the lower limb and body mass, and relatively homogeneous in relation to the their weight.